Territorial conflict over land use in the district of Buenaventura: a mutating territory (2022)
This article shows the territorial conflict generated by port use and urban use in the District of Buenaventura. This phenomenon shows an urban mutation that has produced unplanned transformation processesin the territory. To deal with it, a recount of the port conditions of the city and its behavior in the national economy is made, then a brief review of urban evolution over time is presented, followed by the current trends that motivate the transformations of the territory. Finally, some considerations are raised as a conclusion to the situations discussed